2000
DOI: 10.1111/j.1530-0277.2000.tb04589.x
|View full text |Cite
|
Sign up to set email alerts
|

The Alcohol Use Disorders Identification Test (AUDIT) and Carbohydrate‐Deficient Transferrin (CDT) in a Routine Workplace Health Examination

Abstract: The present findings suggest that AUDIT and CDT are complementary instruments for alcohol screening in a routine workplace health examination, and each has value for identifying a different segment of the risky drinking population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 35 publications
2
29
3
Order By: Relevance
“…In a recent Swedish study conducted in a workplace, in which blood tests for CDT were performed during a routine health examination, the prevalence of high alcohol consumption among men was 8.9% (11). This correlates well with the general view that:/10% of the Swedish population (13% of males and 5% of females) over-consume alcohol, as revealed by a questionnaire survey conducted at a number of primary healthcare centres (12).…”
Section: Introductionmentioning
confidence: 61%
“…In a recent Swedish study conducted in a workplace, in which blood tests for CDT were performed during a routine health examination, the prevalence of high alcohol consumption among men was 8.9% (11). This correlates well with the general view that:/10% of the Swedish population (13% of males and 5% of females) over-consume alcohol, as revealed by a questionnaire survey conducted at a number of primary healthcare centres (12).…”
Section: Introductionmentioning
confidence: 61%
“…Employees who were scheduled for a regular health examination at the company health service were given the opportunity to undergo a voluntary alcohol screening with the Alcohol Use Disorders Identification Test (AU-DIT) (19 ) and by serum CDT measurement. Those who screened negative on the AUDIT (i.e., a score Ͻ8 for men and Ͻ6 for women) (20 ) and had no indication of excessive drinking in the alcohol consumption subscale (questions no. 1-3) (21 ) were used for this study.…”
Section: Materials and Methods Serum Samplesmentioning
confidence: 99%
“…Future studies might consider combining the AUDIT with alcohol biomarkers to screen for problems in individuals with AUDIT scores that are open to question. A thoughtprovoking study suggesting the potential value of using biomarkers in conjunction with the AUDIT was conducted by Hermansson et al (2000). In a routine occupational health exam study using at-risk drinking as a criterion this research group found that 18% of the subjects were positive on either the AUDIT or carbohydrate deficient transferrin, a highly specific alcohol biomarker.…”
Section: Audit Issues In Particular Need Of Further Researchmentioning
confidence: 99%